How will the Chinese Certified Emission Reduction scheme save cost for the national carbon trading system?. (15th August 2019) - Li, Lixu; Ye, Fei; Li, Yina; Chang, Ching-Ter
Abstract: As an important supplementary mechanism to the Emissions Trading Scheme (ETS), the Chinese Certified Emission Reduction (CCER) scheme is of profound significance for achieving low-cost emission reduction and renewable energy goal. However, limited literature discusses the role of the CCER scheme. To explore to what extent will the CCER scheme save cost for China's carbon trading system, this paper establishes a two-level decision sub-game led by the national government and compares the cost-saving effect before and after introducing the CCER scheme. The empirical results from China confirm the cost-saving effect of the CCER scheme while achieving the homogeneity and equivalence of carbon emission quotas and CCER quotas are the prerequisite for the minimum national aggregate costs. The equilibrium CCER trading price is linked to three factors, including the offset rate of CCER quotas, the total carbon emission quotas and the reciprocal of the declaration cost coefficient. Depending on the actual situation in China, the ceiling offset rate of CCER quotas should not exceed 6%. Even so, the national government still needs to clarify the potential provinces and direction of CCER projects to ensure that the actual offset rate could be as close as possible to the optimal value. These findings can provide guidance for policy makers in the design of the national carbon trading system. Highlights: A two-level decision sub-game led by the central government is established. The cost-saving effect of the CCER scheme is confirmed. The optimal and ceiling offset rate of CCER quotas is obtained. The development potential and direction of CCER projects are discussed.